Heterogeneous object modeling with material convolution surfaces. (May 2015) - Gupta, Vikas; Tandon, Puneet
Abstract: The possibility to attain diverse applications from heterogeneous objects calls for a generic and systematic modeling approach for design, analysis and rapid manufacturing of heterogeneous objects. The available heterogeneous object modeling techniques model simple material-distributions only and just a few of them are capable of modeling heterogeneous objects with complex geometries. Even these approaches have also, at time, shown some glitches while modeling complex objects with compound and irregular material variations. This paper unfolds the development of a stand-alone convolution surface-based modeling approach to model complex heterogeneous objects with multi-functional heterogeneities, entailing stratified sub-analytic boundary-representation, convolution material primitives, membership functions and material-potential functions. One-dimensional (associative and non-associative) and compound two-and three-dimensional material-distribution schemas are formulated and outlined to model simple, compound and irregular material-distributions in simple/complex geometry objects. The paper also illustrates a few examples of modeling complex heterogeneous objects by implementing the approach using specialized languages and software tools. Highlights: A material convolution surface-based approach is presented for modeling complex heterogeneous objects. Complex one-dimensional material-distributions are modeled with material primitives and field functions. Schema for compound and irregular heterogeneities in two-and three-dimensions is formulated and outlined. We report a few examples of complex heterogeneous object modeling for the validation of proposed approach.